Curriculum Policies at Language Departments in British schools in the UAE: From Theory into Practice. - HUSSEIN, MUNA (2023)
Curriculum policies are a fundamental foundation for the establishment of educational framework from primary to secondary level. When there are sound policies guiding the curriculum, it is. very easy to implement the curriculum in schools. An effective curriculum provides teachers, students, school leaders and community stakeholders with a measurable plan and structure to deliver quality education. The curriculum sets out the learning outcomes, standards, and core competencies that students need to demonstrate before they progress to the next level. This study focuses on curriculum policies at British schools in the Emirate of Dubai, The United Arab Emirates. The primary purpose of this research is to provide insights into how curriculum policies govern school curriculums in language departments, particularly in Arabic language learning departments. The literature related to this study provides background knowledge on the past and current policy position in determining the effectiveness of language curricula in the UAE. A mixed methods approach was used in this study to measure the competence of the school administrators through quantitative and qualitative data. This has involved an investigation of 5 British schools in Dubai through interviews in order to get a clear picture of how the curriculum policies are being followed. The combined results of the quantitative and qualitative analysis show a gap between the policy and its actual implementation in language areas. The leadership of the school is therefore required to see to it that strong principles are applied and that such policies are continually monitored in the language departments of all British schools in Dubai.